Risk factors for tuberculosis: diabetes, smoking, alcohol use, and the use of other drugs - Silva, Denise Rossato; Muñoz-Torrico, Marcela; Duarte, Raquel; Galvão, Tatiana; Bonini, Eduardo Henrique; Arbex, Flávio Ferlin; Arbex, Marcos Abdo; Augusto, Valéria Maria; Rabahi, Marcelo Fouad; Mello, Fernanda Carvalho de Queiroz (Jornal brasileiro de pneumologia, 2018)
ABSTRACT Tuberculosis continues to be a major public health problem. Although efforts to control the epidemic have reduced mortality and incidence, there are several predisposing factors that should be modified in order to reduce the burden of the disease. This review article will address some of the risk factors associated with tuberculosis infection and active tuberculosis, including diabetes, smoking, alcohol use, and the use of other drugs, all of which can also contribute to poor tuberculosis treatment results. Tuberculosis can also lead to complications in the course and management of other diseases, such as diabetes. It is therefore important to identify these comorbidities in tuberculosis patients in order to ensure adequate management of both conditions. RESUMO A tuberculose continua a ser um importante problema de saúde para a humanidade. Embora os esforços para controlar a epidemia tenham reduzido sua mortalidade e incidência, há vários fatores predisponentes a ser controlados a fim de reduzir a carga da doença. Este artigo de revisão aborda alguns dos fatores de risco associados à infecção por tuberculose, como diabetes, tabagismo, uso de álcool e uso de outras drogas, que podem também contribuir para maus resultados do tratamento da tuberculose. A tuberculose pode levar a complicações no curso e no manejo de outras doenças, como o diabetes. Portanto, é importante identificar essas comorbidades em pacientes com tuberculose a fim de assegurar um manejo adequado de ambas as condições.